HUBUNGAN PERSEPSI PESERTA JAMKESMAS TENTANG PELAYANAN KESEHATAN DENGAN TINGKAT KECEMASAN DI PUSKESMAS RAWAT INAP KALIWIRO KABUPATEN WONOSOBO - Untung E.P; Herniyatun -; Sarwono - (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
To support the success of health care and alleviate health care costs for society, the government in cooperation with PT. Asuransi kesehatan (Health Insurance) holds a Community Health Insurance program (Jamkesmas). The study was aimed to determine the correlation between Jamkesmas participants' perceptions of health services with the level of anxiety at the Inpatient Kaliwiro Health Center. The study was conducted descriptively using cross sectional approach. The samples were 32 respondents taken by using accidental sampling. Chi-square was used to test the statistic. The result showed that Most of the participants' perceptions felt less satisfied with health services at the health center (15 respondents or 46.9%). Most of the respondents had a mild anxiety (15 respondents or 46.9%). Chi-Square obtained ρ = 0.000. The value ρ <α (0.000 <0.05) means that there was a correlation between Jamkesmas participants' perceptions of health services with the level of anxiety. Keywords  : Anxiety, health service, Jamkesmas, perception.